CALCULATION AND DESIGN OF EARTHQUAKE RESISTANT GROUNDS - Khusanboy Turdikulov (Western European Studies, 2024)
In this article, the general rules for the calculation and design of earthquakerelated floors, the strength of the construction site to the earthquake, the method of earthquakerelated floors, changes in the indicators of strengthening the grunts under the influence of an earthquake, measures aimed at increasing the earthquake stability of the floors.
Keywords: Earthquake; ground; calculation; design